Simulation of Mobile LoRa Gateway for Smart Electricity Meter - Sugianto Sugianto; Azwar Al Anhar; Ruki Harwahyu; Riri Fitri Sari (IAES Indonesia Section, 2018)
LoRa is a viable connectivity technology for smart electricity meter. In addition to measuring electricity usage, a smart electricity meter enables many features for smart grid, safety, etc. LoRa is advertised to be capable in very long range transmission and low power consumption. However, LoRa uses sub 1 GHz unlicensed spectrum. In the era of connected smart things, this spectrum is very crowded and will be even more crowded. In this paper we propose the use of mobile LoRa gateway for smart electricity meter. With mobile LoRa gateway, the transmission range can be decreased. Thus, LoRa end devices can save more power and nearby systems can reuse the same band with less interference. We study the performance via simulation using modified LoRaSim. The result shows that the performance of LoRa mobile gateway can be achieved.